2009
DOI: 10.1098/rstb.2009.0077
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of vertebrate rod and cone phototransduction genes

Abstract: Vertebrate cones and rods in several cases use separate but related components for their signal transduction (opsins, G-proteins, ion channels, etc.). Some of these proteins are also used differentially in other cell types in the retina. Because cones, rods and other retinal cell types originated in early vertebrate evolution, it is of interest to see if their specific genes arose in the extensive gene duplications that took place in the ancestor of the jawed vertebrates (gnathostomes) by two tetraploidization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
116
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(127 citation statements)
references
References 103 publications
11
116
0
Order By: Relevance
“…Of the five amphioxus c-type opsins, none clusters in phylogenetic tree within the group of the vertebrate visual and non-visual c-opsins (Pantzartzi et al, 2017). This is in agreement with the proposed evolution of genes involved in vertebrate phototransduction cascade after two rounds of whole genome duplication (2RWGD) that occurred after the split of amphioxus lineage and lineage leading to vertebrates (Lamb and Hunt, 2017;Lamb et al, 2016;Larhammar et al, 2009). Group4 amphioxus opsins representing neuropsins and putative Go-coupled opsins (a group of opsins signaling through the Gao subunit of trimeric G proteins) are of special interest.…”
Section: Opsins As Key Molecular Determinants Of Light Detection In Asupporting
confidence: 74%
See 1 more Smart Citation
“…Of the five amphioxus c-type opsins, none clusters in phylogenetic tree within the group of the vertebrate visual and non-visual c-opsins (Pantzartzi et al, 2017). This is in agreement with the proposed evolution of genes involved in vertebrate phototransduction cascade after two rounds of whole genome duplication (2RWGD) that occurred after the split of amphioxus lineage and lineage leading to vertebrates (Lamb and Hunt, 2017;Lamb et al, 2016;Larhammar et al, 2009). Group4 amphioxus opsins representing neuropsins and putative Go-coupled opsins (a group of opsins signaling through the Gao subunit of trimeric G proteins) are of special interest.…”
Section: Opsins As Key Molecular Determinants Of Light Detection In Asupporting
confidence: 74%
“…It was shown that GNAT can be found only in the genomes of vertebrates, and it most likely originated by tandem duplication of the GNAI gene. Ancient GNAT then underwent quadruplication during the 2RWGD (Lamb and Hunt, 2017;Lamb et al, 2016;Larhammar et al, 2009). In vertebrates two different GNATs (GNAT1 and GNAT2) participate in rod and cone phototransduction, respectively.…”
Section: Frontal Eyementioning
confidence: 99%
“…Rod and cone transducin are thought to originate via duplication from one ancestral gene (Larhammar et al, 2009) and both have been shown to function with all opsins (Sakurai et al, 2007); therefore, the presence and preservation of rod transducin in the photoreceptor supports the theory that this is indeed a transmuted rod and not a cone photoreceptor co-opting rhodopsin expression. Because the retinas were not dark adapted prior to euthanasia, we can presume that under normal photopic light conditions, P. melanoleucus rod transducin is cycled out of the outer segment of the cone-like rod, a distinct rod property Rosenzweig et al, 2007).…”
Section: Discussionmentioning
confidence: 60%
“…It had been assumed that vertebrates utilize the same pathway for regenerating rod and cone visual pigment (11-cis RAL). Interestingly, rods and cones do partly utilize different subtypes of enzymes in phototransduction (for example different subunits of the transducin protein (Larhammar et al, 2009)). Considering this specialization and the apparent differences in cone versus rod light sensitivities and kinetics, it has been tempting to speculate that cone and rod photoreceptors might use cell type-specific enzymes/pathways for processes involving the retinoid cycle as well.…”
Section: Vertebrate Duplex Retinamentioning
confidence: 99%